Relative Change in SI Engine’s Emission and Performance Parameters Using New Locally Made Octane Enhancer - Sheet, Eman Ali Ehsan (Journal of Petroleum Research and Studies, 2017)
In this study, a new gasoline Octane enhancer was made in Al-Doura refinery in Baghdad and was used with the Iraqi pool gasoline. The main objective of this study was to find an Octane booster to the low Octane Gasoline produced by Al-Doura refinery that does adversely affect its chemical, physical or combustion properties. This additive was then added to gasoline in different percentages (2.5% till 15% Vol) and the blend’s properties e.g. calorific value, density, Octane number (RON and MON), gum content, sulfur content were measured. These blends were then tested against the performance of the original pool gasoline using previously calibrated and tested software. The relative change in the engine performance was then observed and compared. It was found that the octane number of gasoline significantly improved after addition of the additive, its gum content decreased, its calorific value decreased while the sulfur content was slightly increased. No major change in the engine performance was noticed except for the decrease in peak cylinder temperature and the sulfur dioxide and nitrogen oxides level at 2.5% then increased with additives.